Oxygen active form production and endothelial system status in coronary heart disease patients with reduced contractility function - L. A. Bokeria; V. E. Malikov; M. A. Arzumanyan; O. V. Vladytskaya; G. V. Sukoyan (Российский кардиологический журнал, 2006)
.